Kelemahan Berlapis Pada Ibu (Waḥnan ‘Alā Waḥnin) Dalam QS. Luqmān: 14 dan Relevansinya Dengan Fenomena Baby Blues - Azkia Zahra; Farhan Indra (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the meaning of waḥnan ‘alā waḥnin in QS. Luqmān 31:14 based on classical and contemporary Qur’anic interpretations and examine its relevance to the phenomenon of baby blues from a modern psychological perspective. This qualitative study employs a taḥlīlī exegetical approach integrated with modern psychology. Data were obtained through a literature review of the Qur’an and Qur’anic commentaries, complemented by semi-structured interviews with postpartum mothers selected through purposive sampling. Data were analyzed descriptively and qualitatively by integrating interview findings, exegetical interpretations, and psychological literature. The findings demonstrate that waḥnan ‘alā waḥnin represents maternal weakness as a gradual and layered condition encompassing physical, emotional, and psychological dimensions from pregnancy through childbirth and the postpartum period. Interview findings reveal experiences of fatigue, mood changes, sadness, anxiety, emotional pressure, and difficulties adapting to the new role of motherhood. These findings indicate a significant relevance between the concept of waḥnan ‘alā waḥnin and baby blues, particularly in describing maternal vulnerability and psychological burdens during the postpartum period, although the two concepts are not conceptually identical. The study confirms that the Qur’anic perspective can enrich the understanding of postpartum maternal vulnerability by emphasizing empathy, family support, and greater attention to maternal mental health.